Interaction of Adipocyte Metabolic and Immune Functions Through TBK1 - Zhao, Peng; Saltiel, Alan R. (Frontiers in Immunology, 2020)
Adipocytes and adipose tissue play critical roles in the regulation of metabolic homeostasis. In obesity and obesity-associated metabolic diseases, immune cells infiltrate into adipose tissues. Interaction between adipocytes and immune cells re-shapes both metabolic and immune properties of adipose tissue and dramatically changes metabolic set points. Both the expression and activity of the non-canonical IKK family member TBK1 are induced in adipose tissues during diet-induced obesity. TBK1 plays important roles in the regulation of both metabolism and inflammation in adipose tissue and thus affects glucose and energy metabolism. Here we review the regulation and functions of TBK1 and the molecular mechanisms by which TBK1 regulates both metabolism and inflammation in adipose tissue. Finally, we discuss the potential of a TBK1/IKKε inhibitor as a new therapy for metabolic diseases.